Asas-Asas Pembentukan Peraturan Perundang-Undangan yang Baik: Sebuah Tinjauan Kritis - Dachran S. Busthami (SIGn Jurnal Hukum, 2022)
This study aims to examine and analyze the fundamentality of the principles of good legislation forming. This study uses normative legal research with historical, conceptual, and statute approaches. The collection of legal materials is carried out using a literature study technique. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that the principles of law are the spirit or soul of the law. The law will exist and grow in society, only and if the law is rooted in the principles of law. Meanwhile, legislation means written regulations containing generally binding legal norms. So that the principles of good legislation forming are principles of law that provide guidelines and guidance for formulating the contents of regulations. Therefore, it is recommended for legal academics to have a construction of thought based on the principles of law. In addition, the Government must ensure every legal academic’s competence when making academic manuscripts of draft legislation. In this case, the law-based state must achieve social justice for Indonesia’s people.